2011
DOI: 10.1007/s10344-011-0585-z
|View full text |Cite
|
Sign up to set email alerts
|

Quota hunting of Eurasian lynx in Norway: patterns of hunter selection, hunter efficiency and monitoring accuracy

Abstract: Harvesting large carnivores is often a controversial issue and thus requires a higher precision than other types of recreational harvest. Despite this, management programmes are often initiated based on very limited knowledge about the state of the population and the composition and magnitude of the harvest. Here we analyse patterns of lynx harvest in Norway based on harvest data from 1994 to 2009. We found clear signs of sex-biased harvest rates, with males generally being more at risk. Further, harvest morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…Just because lynx can use an area does not automatically imply that their population has a positive or stable trend (Stapleton et al, 2014), and indeed our earlier work has shown that lynx are more vulnerable to being shot in areas with higher road densities (Basille et al, 2013). However, most lynx mortality in Norway is due to legal hunter harvest (Andrén et al, 2006) which is regulated within an adaptive management system with annual monitoring and quota setting (Linnell et al, 2010;Nilsen et al, 2012) implying that the fate of lynx in the study region is amenable to management control. Results such as these are important to frame the large carnivore conservation discourse because they show that there is no automatic connection between lynx and wilderness .…”
Section: Conclusion and Management Implicationsmentioning
confidence: 95%
“…Just because lynx can use an area does not automatically imply that their population has a positive or stable trend (Stapleton et al, 2014), and indeed our earlier work has shown that lynx are more vulnerable to being shot in areas with higher road densities (Basille et al, 2013). However, most lynx mortality in Norway is due to legal hunter harvest (Andrén et al, 2006) which is regulated within an adaptive management system with annual monitoring and quota setting (Linnell et al, 2010;Nilsen et al, 2012) implying that the fate of lynx in the study region is amenable to management control. Results such as these are important to frame the large carnivore conservation discourse because they show that there is no automatic connection between lynx and wilderness .…”
Section: Conclusion and Management Implicationsmentioning
confidence: 95%
“…Reconstructions of population size of lynx (Nilsen et al . ) and genetic capture–mark–recapture of wolverine (Brøseth et al . ), however, reveal that the national monitoring programme of lynx family groups and wolverine reproductions reflect population sizes well.…”
Section: Methodsmentioning
confidence: 99%
“…The quota decision‐making is also highly relevant for lynx management, as the level of quota filling in the annual lynx harvest is high in the study area, on average 80% and 77% of the quota is filled in northern Sweden and Norway (Nilsen et al. , Bischof et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Nilsen et al. () found a good fit ( r = 0.84) between monitored population size and reconstructed population size for Norway. Thus, the lynx monitoring provides an index of all lynx in an area.…”
Section: The Study System and Materialsmentioning
confidence: 95%